A class of azocarbazole‐based carboxylates: High‐efficiency ionic unimolecular photobase generators for thiol‐epoxy click polymerization under blue light. Issue 23 (28th September 2021) - Xu, Can; Wu, Xiang; Xiong, Ying; Li, Zhen; Tang, Hongding
Abstract: Two new unimolecular azocarbazole‐based visible photobase generators (Ac‐C‐Base) with different strong bases such as 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) and 1, 1, 3, 3‐tetramethylguanidine (TMG) as the potential active species were prepared. Their structures were confirmed by 1 H NMR, 13 C NMR, and HR‐MS. According to the photolysis and EPR results, Ac‐C‐Base could generate free radicals and strong bases simultaneously through the photodecarboxylation mechanism under 455 nm LED irradiation. Thus they can effectively catalyze the thiol‐epoxy polymerization without post exposure baking under light exposure. In addition, the Ac‐C‐TBD containing a stronger base shows a faster polymerization rate and higher epoxy conversion. Abstract :